2022
DOI: 10.1111/soru.12400
|View full text |Cite
|
Sign up to set email alerts
|

Is agriculture an occupation or a sector? Gender inequalities in a European context

Abstract: This article focuses on inequalities in agriculture in the European Union. We examine the mismatch between European legislation on employment and any rigorous interrogation of women's employment position in agriculture. Our central argument is that this occurs because agriculture is seen as a sector rather than an occupation. DG AGRI is responsible for European agricultural and rural development policies. DG EMPLOYMENT does not have oversight for the agricultural workforce in the same way as other occupations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Since 1996, the European Commission has adopted the dual approach of targeted measures to achieve gender equality alongside gender mainstreaming. Gender mainstreaming basically means including a gender perspective into all stages of policy design in all EU policies (European Commission, 2020;Shortall & Marangudakis, 2022;Daly, 2005). Extensive research and reports from EU institutions have systematically found that the EU institutions themselves, as well as Member States, do not implement gender mainstreaming (ECA, 2020(ECA, , 2021EPRS, 2021;Shortall & Marangudakis, 2022;Spehar, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since 1996, the European Commission has adopted the dual approach of targeted measures to achieve gender equality alongside gender mainstreaming. Gender mainstreaming basically means including a gender perspective into all stages of policy design in all EU policies (European Commission, 2020;Shortall & Marangudakis, 2022;Daly, 2005). Extensive research and reports from EU institutions have systematically found that the EU institutions themselves, as well as Member States, do not implement gender mainstreaming (ECA, 2020(ECA, , 2021EPRS, 2021;Shortall & Marangudakis, 2022;Spehar, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Gender mainstreaming basically means including a gender perspective into all stages of policy design in all EU policies (European Commission, 2020;Shortall & Marangudakis, 2022;Daly, 2005). Extensive research and reports from EU institutions have systematically found that the EU institutions themselves, as well as Member States, do not implement gender mainstreaming (ECA, 2020(ECA, , 2021EPRS, 2021;Shortall & Marangudakis, 2022;Spehar, 2012). In other words, there is a weak commitment to addressing gender equality, and consequently, the tools and processes advocated at the EU level are not enacted.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations